Comparison of Phytoremediation and Filtration for Diamond-mine-tailings Water Treatment - Noor, M. Hafidhuddin; Rahman, Mijani; Gazali, Akhmad; Kania, Nia; Rahma, Aulia; Rampun, Erdina L.A.; Pratiwi, Amalia E.; Elma, Muthia (UI Scholars Hub, 2020)
The water pollution caused by diamond mine activities can kill aquatic life. In this work, we used phytoremediation and filtration to treat pond water polluted by the tailings of a diamond mine located in South Kalimantan, Indonesia. Einchhornia crassipes (water hyacinth) was utilized as the biomass for the phytoremediation process. Gravel (10–15 mm) and sand (0.1–1 mm) were used as filter media in the simple filtration setup, using an up-flow system (bottom to top). In the experiment, 16 L of diamond tailing water was poured into five phytoremediation reactors (each 60 L in volume), which were then tested over seven days. A pretreatment analysis of the tailings water showed that its biochemical oxygen demand (BOD) of 8.9 mg L−1 and chemical oxygen demand (COD) of 22 mg L−1 exceeded the national maximum standards of 2 mg L−1 and 10 mg L−1, respectively. The experimental results demonstrate that both phytoremediation and filtration could increase the dissolved oxygen concentration (4.7 mg.L−1) and reduce the BOD (3.2 mg.L−1), COD (6.5 mg.L−1), Fe (0.6 mg.L−1), Mn (0.16 mg.L−1), and ammonia (0.63 mg.L−1) concentrations from those measured in the raw diamond-mine-tailings water. The phytoremediation performance was better than that of filtration. The COD values were successfully reduced to the permissible limit, although the other parameters still failed to meet the government water quality regulation requirements.